Solve the following formula for t.

Upper U equals Upper M left parenthesis 1 plus rt right parenthesis
Question content area bottom
Part 1
The solution is tequals
  
enter your response here. ​(Simplify your​ answer.)

1 answer

To solve the formula \( U = M(1 + rt) \) for \( t \), follow these steps:

  1. Divide both sides by \( M \):
    \[ \frac{U}{M} = 1 + rt \]

  2. Subtract 1 from both sides:
    \[ \frac{U}{M} - 1 = rt \]

  3. Rewrite the left side:
    \[ \frac{U - M}{M} = rt \]

  4. Divide both sides by \( r \):
    \[ t = \frac{U - M}{Mr} \]

So, the solution for \( t \) is:
\[ t = \frac{U - M}{Mr} \]